(3TQM GdLeds - (3CHhGdMSf Ydj Hf eDef Hf eMeO GdNVQej GdETHjdj GdeYQha HGHf YUahQs; (3GdRLGLj , CHh GdbGSe,J (B337 (3g` s
(3ChdgG (B:s
(3bGd CHhGdbGSe(B: (3CbSGe GdcdGe KdGKI(B: (3GSe haYd hMQa CbSGe GdcdGe eVGa heVGa Edjg s
(3BNQgG (B:s
(3aEf cGf GdehVY ehVY OaY GJHYJg HGdQaY, hEf cGf ehVY fUH CJHYJg HGdfUH bO JeJ gPG GdcJGH HYhf s
(3aj GdeYgO fSNJGf CNQJGf Qbe (B" 70 (3h (B71 "s
(3egedI GdfbW CMjGfkGs
(3hLGA aj BNQgG HNW eNGda eJCNQ CfgG cJHJ aj SfI (B575(3g`` dG JfGSH SfI (B669(3g` GdJj gj haGI GdTGQM GHf YUahQs
(3fSNI KGdKI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs